Measuring Spatial Accessibility of Healthcare Services in Calgary (poster). (December 2017) - Khakh, Amritpal Kaur; Fast, Victoria
Abstract : Background: Access to healthcare is one of the deterministic factors in an individual's quality of life. Ideally, access to healthcare facilities should be optimized for walkability and/or public transit, for all people, regardless of (dis)ability. However, spatial accessibility of health services in Calgary is often difficult to measure since there could be more than one walking or transit route from the neighborhood to the healthcare facility. Aim: The focus of this research is to map the spatial accessibility of healthcare facilities within Calgary census tracts, with a focus on vulnerable groups, including elderly, children, visually impaired pedestrians, and persons with disabilities. The spatial accessibility of healthcare facilities is measured by various proxies for accessible walkability, including sidewalks, public transit, and accessible pedestrian signal locations. Methods: Geographic Information Systems (GIS) are used to measure spatial accessibility to delineate spatial patterns and trends in the accessibility of health services in Calgary. The data sources for this study include Calgary's 2016 census, health facilities data from the Alberta Health Services data portal, transit and walkability routes from the City of Calgary Open Data Catalogue, and the accessible pedestrian signal locations data. Specifically, the two-step floating catchment area approach is used to analyze the interactions between the built environment and the accessibility to healthcare. Results: The results of this research developed an accessibility index as a proxy for spatial access to healthcare services. The cartographic outputs effectively illustrate the ease of access to the healthcare facility, including the interaction of transit, walkable routes, and the accessible pedestrian signal locations in Calgary. Conclusion: From the results obtained through this study, specific improvements can be made to the built environment to enhance the healthcare accessibility, by car-free means, for all residents inclusively. The ultimate aim of this research is to disseminate our results to empower stakeholders like Alberta Health Services, to direct their respective services towards inclusively enhancing Calgary's spatial accessibility to healthcare.